Diet supplementation with the cis-9,trans-11 conjugated linoleic acid isomer affects the size of adipocytes in Wistar rats - Lopes, Paula A. (2015)
Previous reports have demonstrated that conjugated linoleic acid (CLA) acts on body fat accumulation in a variety of animal models. The aim of the present study was to investigate the effect of cis (c)-9,trans (t)-11 and t10,c12 CLA isomers on the number and size of adipocytes from the inguinal and retroperitoneal fats in Wistar male rats. A 5.1% palm oil-based diet was supplemented with CLA isomers as follows: 0.6% of c9,t11, 0.6% of t10,c12, 1.3% of c9,t11 and t10,c12 isomers in mixture, and a control nonsupplemented group for comparative purposes. Fat tissues were prepared on microscope slides for histologic examination using an image-analysis software to count the number of adipocytes and measure cell sizes. The results showed that CLA isomers did not affect (P .05) either final body and fat depot weights or serum lipids (with the exception of triacylglycerols) and adipocytokines (leptin and adiponectin). Animals fed the c9, t11 CLA isomer diet showed larger adipocytes when compared to other groups. Independently of the CLA dietary treatment, retroperitoneal fat showed larger adipocytes (3319 mu m(2)) and therefore a smaller number of adipocytes per unit of area, compared to inguinal fat (3055 mu m(2)) Taken together, the data suggest that a palm oil-based diet supplemented with the c9,t11 CLA isomer in Wistar rats, in contrast to the t10,c12 isomer and the mixture of both isomers, increases adipocyte dimensions in inguinal and retroperitoneal fat depots, while having a minor effect in serum lipids and adipocytokines. (c) 2008 Elsevier Inc. All rights reserved.